The Costs and Benefits Analyses of Peg Regime with Indian Currency (The International Research Journal of Management Science, 2016)
This paper aims to provide a comprehensive idea on peg regime where its actual costs and benefits have been analyzed. The object of the study is to give an overview towards the country’s economy and where it is facing due to the involvement of peg regime. Many reviews have been accomplished in this matter and people have written a lot about the peg regime, also about its misalignment. But after consultation with the scholars and traders anything spoken would not be valid unless it has been presented with empirical analysis for any kind of change to be forwarded in order to review the existing peg regime. This paper has solely highlighted the cost and benefits and it does not challenge any economists or scholars who have different views regarding the matter.